HISTORY OF GENDER RELATIONS IN UZBEKISTAN - Ahrorova Madina Rahmatovna (American Journals Publishing, 2023)
The issue of gender equality is one of the social relations that are well established not only in Europe, but also in our country. In particular, in this regard, the Law of the Republic of Uzbekistan "On guarantees of equal rights and opportunities for women and men" adopted on September 2, 2019 was approved as a legal protection and legal guarantee aimed at the place of women in society.
Keywords: Mentality, Avesto, family, Akhuramazda, Koran, Khadis